Ascorbic acid mitigation of water stress-inhibition of root growth in association with oxidative defense in tall fescue (Festuca arundinacea Schreb.) - Xu, Yi; Xu, Qian; Huang, Bingru (Frontiers in Plant Science, 2015)
Root growth inhibition by water stress may be related to oxidative damages. The objectives of this study were to determine whether exogenous application of ascorbic acid (ASA) could mitigate root growth decline due to water stress and whether ASA effects on root growth could be regulated through activating non-enzymatic or enzymatic antioxidant systems in perennial grass species. Tall fescue (Festuca arundinacea Schreb. cv. ‘K-31’) plants were grown in nutrient solution, and polyethylene glycol (PEG)-8000 was added into the solution to induce water stress. For exogenous ASA treatment, ASA (5 mM) was added into the solution with or without PEG-8000. Plants treated with ASA under water stress showed significantly increased root growth rate, and those roots had significantly lower content of reactive oxygen species (ROS) (H2O2 and O2- content) than those without ASA treatment. Malondialdehyde content in root tips treated with ASA under water stress was also significantly reduced compared with those under water stress alone. In addition, free ascorbate and total ascorbate content were significantly higher in roots treated with ASA under water stress than those without ASA treatment. The enzymatic activities for ROS scavenging-related genes were not significantly altered by ASA treatment under water stress, while transcript abundances of genes encoding superoxide dismutase, catalase, ascorbate peroxidase, glutathione reductase, dehydroascorbate reductase, and monohydroascorbate reductase showed significant decreases in the root elongation zone and significant increases in the root maturation zone treated with ASA under water stress. Transcripts of genes for expansins and xyloglucan endotransglycosylases showed increased abundances in ASA-treated root maturation zone under water stress, indicating that ASA could accelerated cell wall loosening and cell expansion. The results suggested that exogenous treatment of roots with ASA enhanced root elongation under water stress, which could be attributed by increasing non-enzymatic antioxidant production, suppressing ROS toxicity and up-regulating gene expression of cell-wall loosening proteins controlling cell expansion.